Nutritional characterization and production of biomass of Sambucus peruviana, Sambucus nigra and Morus alba in a forage bank (2019)
Forage banks are strategies for cultivating shrub species at high planting densities that guarantee the availability of food for ruminants on farms. Therefore, the production of leaves and the nutritional quality of mulberry (Morus alba L.), tilo (Sambucus peruviana) and sauco (Sambucus nigra L.) without fertilization in Boyacá (2700 masl) were evaluated in a completely random desing. An analysis of variance was performed (Anova) and where there were significant differences the Tukey test was applied (p <0.05). The results were: leaf area per plant of 81.82 ± 0.01cm2,131.37 ± 0.01cm2, 89.98 ± 0.01cm2; weight of individual green forage 1.73 ± 0.05 kg, 2.23 ± 0.05 kg, 1 ± 0.04 kg; dry matter (MS) 30.8 ± 0.05%, 20.2 ± 0.06%, 20.1 ± 0.06%; crude protein (PC) 14.62 ± 0.01%, 14.2 ± 0.06%, 13.4 ± 0.05%; Ethereal extract (EE) 0.85 ± 0.01%, 1.8 ± 0.05, 1.4 ± 0.05%; ashes (CEN) 8.6 ± 0.05%, 1.8 ± 0.05%, 10.07 ± 0.01%; crude fiber (FC) 18.97 ± 0.01%, 17.92 ± 0.18%, 17.8 ± 0.05%; neutral detergent fiber (NDF) 37.8 ± 0.05%, 29.9 ± 0.05%, 23.1 ± 0.05%; acid detergent fiber (FDA) 29.4 ± 0.05%, 47.3 ± 0.05%, 34.8 ± 0.05%, for mulberry, linden and elder respectively. Biomass and nutritional quality varied by species, highlighting lime with the highest production of green fodder (6.9 tons / ha) and protein of 0.19 tons / ha (p <0.05).